Conformally Flat Pseudoprojective Symmetric Spacetimes in fR, G Gravity. (25th March 2022) - De, Uday Chand; Shenawy, Sameh; Syied, Abdallah Abdelhameed; Turki, Nasser Bin
Abstract : Sufficient conditions on a pseudoprojective symmetric spacetime PPS n whose Ricci tensor is of Codazzi type to be either a perfect fluid or Einstein spacetime are given. Also, it is shown that a PPS n is Einstein if its Ricci tensor is cyclic parallel. Next, we illustrate that a conformally flat PPS n spacetime is of constant curvature. Finally, we investigate conformally flat PPS 4 spacetimes and conformally flat PPS 4 perfect fluids in f R, G theory of gravity, and amongst many results, it is proved that the isotropic pressure and the energy density of conformally flat perfect fluid PPS 4 spacetimes are constants and such perfect fluid behaves like a cosmological constant. Further, in this setting, we consider some energy conditions.